The Compliance of Young Women at SMPN 1 Makale Utara in Consuming Iron Tablets is Related to Their Level of Knowledge - Margareta Rante Musu; Bahtiar Bahtiar; Baharuddin Baharuddin; Betriana Disik; Yosefa Anggraeni Mateus Paberu (Alliance oh Health Activists (AloHA), 2025)
Iron deficiency anemia is one of the biggest micro problems in Indonesia which occurs in toddlers, school children, pregnant women and teenagers. Adolescence is a transition period from childhood to adulthood and the beginning of the separation of nutritional needs based on gender. This study aimed to analyze the relationship between the level of knowledge and compliance of young women and consuming iron tablets at SMPN 1 Makale Utara. This type of research was analytical observational. Researchers applied a cross-sectional design in this study. Subjects were 50 female students, selected using stratified random sampling technique based on representatives of each class. The measurements of the two variables above were carried out by filling out questionnaires directly by young women. The hypothesis testing was carried out using the Chi-square test. Table 4 shows that the better the level of knowledge, the higher the level of compliance with taking iron tablets. The p value from the results of hypothesis testing was 0.001, so it was interpreted that the level of knowledge was correlated with the level of compliance of young female students in consuming iron tablets. Based on the research results, it could be concluded that the compliance of young women at SMPN 1 Makale Utara in consuming iron tablets is related to their level of knowledge. Keywords: basic research; guide book; beginner researcher; health student